Memaknai Hadis Larangan Makan dan Minum dengan Tangan Kiri di Era Modern (Studi Ma’anil Hadis) - Muhamad Danil; Mugiono; Hedhri Nadhiran (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2024)
This article is entitled “Interpreting the Hadith of the Prohibition of Eating and Drinking with the Left Hand (Study of Ma’anil Hadith), “. It can be seen that eating and drinking are basic human needs, many Muslims will ignore the sunnah of the prophet Saw, in etiquette when eating and drinking it is recommended to use the right hand. Then to overcome the occurrence of irregularities in carrying out islamic law. Hadith should be understood in a way that remains in accordance with the factors related to the hadith. So that the hadith can be understood textually and contextually. The results showed that the meaning contained in the hadith of the  prophet Saw, prohibiting eating and drinking with the left hand with authentic quality, can be used as evidence. The teachings contained in it are a tasyri’iyyah sunnah that must be practiced. The prohibition of eating and drinking using the left hand because it is classified as satnic behavior. Satan and his armies invite people to evil deeds. But in today’s era of increasingly sophisticated develipments, it is very important to educate parents form a young age to make it possible to eat and drink using the right hand.